Flow Analysis for Hydrocarbon Pipeline Engineering - Terenzi, Alessandro; Terenzi, Alessandro (Gulf Professional Publishing, 2022)
Flow Analysis for Hydrocarbon Pipeline Engineering gives engineers a tool to help them determine fluid dynamics. The book describes hydrocarbon fluid transport in pipelines by presenting useful applied thermodynamic derivations specialized for pipelines. All transport phenomena is covered, such as heat, momentum and mass transport. Moving past the fundamentals, the reference addresses the complexity of these fluids and dedicates a chapter on multiphase mixtures, including slugging, hydrates, wax and sand. Rounding out with practical case studies, this book delivers a critical reference for engineers and flow assurance experts that will help them correlate basic fluid principles with applied engineering practices. - Includes discussions on sustainable operations such as CO2 transport in pipelines utilized in carbon capture and hydrocarbon recovery operations - Delivers multiple case studies for practical applications and lessons learned - Describes hydrocarbon fluid transport in pipelines by presenting useful applied thermodynamic derivations specialized for pipelines